Coping Strategy in Counseling Services Through the Eduda Application Program in the Pandemic Period - Raudah Zaimah Dalimunthe; Rosmala Dewi; Evans Libra Sianipar (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2021)
This study aimed to produce teaching materials for effective coping strategies in the implementation of counseling services to students. Teaching materials are made in printed form, then for the benefit of the pandemic, they were arranged in the form of an EDUDA (Education of Drug Adversity) application program. A coping strategy is one of the life skills of the seven skills that are trained in the EDUDA application program design research development using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) carried out for 6 months. The research subjects were 29 students of class X SMA Negeri 17 Medan TA. 2019/2020. Data collection techniques (1) conducting interviews about coping strategy exercises, (2) distributing valid questionnaires via zoom, (3) monitoring the progress of the exercise implementation through WhatsApp (WA). The effectiveness of teaching materials is assessed according to the answer key in each exercise and the questions have a score, the results of the exercise are 27 students have passed the mean percentage of 93.10% and have achieved a very good classification. The conclusion of this study is that this coping strategy teaching material is effective for use in counseling services for class X students of SMA Negeri 17 Medan TA. 2019/2020.